Rheological segmentation of the Cocos slab and its relation with the 2017 Mw8.2 Tehuantepec earthquake - Manea, M.; Manea, V. C.; Yoshioka, S.; Moreno, E. J.; Suenaga, N. (Frontiers in Earth Science, 2025)
Tectonic plates bend and deform when approaching a subduction zone, creating intense faulting and highly variable stress and strain fields across short distances inside the slab. In September 2017, a large Mw8.2 intraplate normal fault occurred in southern Mexico, with an epicentral area located within a seismic gap where no megathrust had struck in more than a century. Despite the relatively young and hot Cocos plate, this seismic episode ruptured almost the entire slab below the brittle–ductile transition zone that normally limits the depth extent of such events. Here, we present a high-resolution thermomechanical model of spontaneous subduction for this area, where bending-induced brittle and ductile deformation and grain plate damage are considered. Modeling results show that the 2017 Mw8.2 Tehuantepec normal fault earthquake occurred due to the reactivation of one of the outer-rise-formed abyssal faults. In addition, the hypocenter was located in a stable, hydrated region of the lithospheric mantle at the transition limit between the elastic and ductile regimes. We found that earthquake rupture orientation is consistent with a region where a clear localized shear band of reduced effective viscosity is predicted. We propose that the rupture of this large intraslab event propagated in the ductile portion of the slab initially by a transformational faulting process, followed by a thermal runaway mechanism at greater depths and higher temperature.